Pengaruh Job Characteristics dan Leader Member Exchange (LMX) Terhadap Work Engagement di PT Elang Perdana Tyre Industry - Nurdiani Komala Dewi; Aji Hermawan; M. Joko Affandi (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Work engagement is an important concept in employee work behavior in organizations. This study aims to examine the direct positive effect of job characteristics and leader-member exchange (LMX) on work engagement and examine the role of LMX as a moderating variable on the influence of job characteristics on work engagement. A total of 395 samples were employees at PT Elangperdana Tire Industry. The model in this study was analyzed by SEM (Structural Equation Modeling) method. The results showed that job characteristics and LMX directly and positively affected the work engagement. In addition, LMX showed a role as a moderating variable that influenced of job characteristics on work engagement. In other words, the better relationship of LMX increased the influence of job characteristics on work engagement.Keywords: job characteristics, leader member exchange, LMX, work engagement, SEMAbstrak: Work engagement merupakan konsep yang penting dalam perilaku kerja karyawan di organisasi. Penelitian ini bertujuan menguji pengaruh positif secara langsung job characteristics dan leader member exchange (LMX) terhadap work engagement dan menguji peran LMX sebagai pemoderasi pada pengaruh job characteristics terhadap work engagement. Sebanyak 395 kuesioner yang dapat diolah dalam penelitian ini dimana sampel diambil dari karyawan di PT Elangperdana Tyre Industry. Pengujian model dalam penelitian ini menggunakan metode SEM (Structural Equation Modeling). Hasil penelitian menunjukkan job characteristics dan LMX mempengaruhi secara langsung dan positif signifikan terhadap work engagement. Selain itu, LMX menunjukkan peran sebagai pemoderasi dalam pengaruh job characteristics terhadap work engagement. Dengan kata lain, semakin baiknya LMX dapat meningkatkan pengaruh job characteristics terhadap work engagement. Kata kunci: job characteristics, leader member exchange, LMX , work engagement, SEM